Effect Of Complementary Acupressure Therapy On Emesis Gravidarum In Pregnant Women Trimester I - Dewi, Rahma Kusuma; Saidah, Halimatus (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Vomiting nausea (Emesis Gravidarum) is a reasonable symptom and often occurs in first trimester pregnancies. Vomiting nausea is caused by increased esterogen hormones, HCG factors, changes in liver glycogen metabolism, and psychological factors. The treatment of vomiting nausea in pregnancy consists of pharmacology and nonfarmalogy. Nonpharmacological therapy is performed by diet setting, emotional support, and acupressure. Nonpharmacological therapy is a type of complementary therapy that can be used as an intervention to overcome nausea, among others: acupressure, acupuncture, relaxation, and therapy. The purpose of this study is to find out the effect of acupressure complementary therapy in reducing vomiting nausea (Emesis Gravidarum) in pregnant women trimester I. The research method used is Quasy Experiment Design with one group pretest and posttest design approach. Sampling techniques use proportional random sampling. Instruments used to measure vomiting nausea are questionnaires. The collected data is analyzed using the Wilcoxon test.